SPECTROSCOPIC INSIGHTS AND PHYSICOCHEMICAL PROPERTIES OF DEEP EUTECTIC SOLVENTS FORMED FROM CHOLINE CHLORIDE AND ORGANIC HYDROGEN BOND DONORS - Indah Puspita Sari; Eti Artiningsih Octaviani; Shefia Dhiya Khansa; Ganjar Fadillah (Analit : Analytical and Environmental Chemistry, 2024)
This study investigates the physicochemical properties and molecular insights of Deep Eutectic Solvents (DES) formed with choline chloride as the hydrogen bond acceptor (HBA) and various organic hydrogen bond donors (HBDs), such as citric acid, glycerol, and glycolic acid. DES were assessed for bioactive compound extraction using Fourier Transform Infrared (FTIR) spectroscopy to analyze hydrogen bonding interactions and by measuring viscosity, density, and water content. Results showed viscosity ranging from 100 to 300 mPa-s and density from 1.05 to 1.45 g/cm ³, depending on the specific HBD. DES formed with glycerol and sorbitol exhibited higher viscosity due to stronger hydrogen bonding, while DES with lactic acid and glycolic acid showed lower viscosity, enhancing fluidity. FTIR spectra revealed shifts in the O—H and C=O stretching bands, indicating complex hydrogen bonding networks. These findings highlight the potential of DES to optimize bioactive compound extraction and their application in the cosmetics industry.